Investigating Geo-disaster Knowledge, Attitude, and Practices among Secondary School Students in Cameron Highlands, Pahang, Malaysia - Nasir bin Nayan, Hanifah binti Mahat, Mohmadisa bin Hashim, Yazid bin Saleh, Zahid bin Mat Said (Tanjung Malim, 2024)
Investigating Geo-disaster Knowledge, Attitude, and Practices among Secondary School Students in Cameron Highlands, Pahang, Malaysia by Nasir bin Nayan, Hanifah binti Mahat, Mohmadisa bin Hashim, Yazid bin Saleh, Zahid bin Mat Said